2003
DOI: 10.1021/ja0351443
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Monofunctional Metalation of Adenine Nucleobase in Guanine- and Thymine-Containing Dinucleotide Sequences by a Cytotoxic Platinum−Acridine Hybrid Agent

Abstract: We have investigated the reactions of [PtCl(en)(ACRAMTU-S)](NO(3))(2) (2) (en = ethane-1,2-diamine; ACRAMTU = 1-[2-(acridin-9-ylamino)ethyl]-1,3-dimethylthiourea, acridinium cation, 1), the prototype of a new class of cytotoxic DNA-targeted agents, with 2'-deoxyguanosine (dGuo) and random-sequence native DNA by in-line liquid chromatography/mass spectrometry (LC/MS) and NMR spectroscopy ((1)H, (195)Pt) to identify the covalent adducts formed by platinum. In the mononucleoside model system, two adducts are obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 38 publications
3
73
0
Order By: Relevance
“…PT-ACRAMTU ([PtCl(en)(ACRAMTU)](NO 3 ) 2 , en = ethylenediamine; Figure 1) and its derivatives show promising activity in vitro in several solid tumors, including ovarian and lung cancer cell lines (1518). While the cellular biology of the parent conjugate is still under investigation, we proposed the unprecedented targeting of adenine residues at 5′-TA sites in the minor groove of DNA by this dual metalating-intercalating agent (19,20) may play an important role in its mechanism of action (2123). Following our interest in small-molecule modulators of transcription, we have now begun to extend our studies to reversible bifunctional intercalators derived from PT-ACRAMTU.…”
Section: Introductionmentioning
confidence: 99%
“…PT-ACRAMTU ([PtCl(en)(ACRAMTU)](NO 3 ) 2 , en = ethylenediamine; Figure 1) and its derivatives show promising activity in vitro in several solid tumors, including ovarian and lung cancer cell lines (1518). While the cellular biology of the parent conjugate is still under investigation, we proposed the unprecedented targeting of adenine residues at 5′-TA sites in the minor groove of DNA by this dual metalating-intercalating agent (19,20) may play an important role in its mechanism of action (2123). Following our interest in small-molecule modulators of transcription, we have now begun to extend our studies to reversible bifunctional intercalators derived from PT-ACRAMTU.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the modified platinum drugs form an array of covalent adducts similar to that formed by cisplatin. However, Bierbach and co-workers have reported the first example of monofunctional adenine adducts being formed by a divalent platinum complex, [PtCl(en)(ACRAMTU-S] (ACRAMTU ¼ 1-[2-(acridin-9-ylamino)ethyl]-1,3-dimethylthiourea), with double-stranded DNA [37]. Furthermore, the authors concluded that the platinum-acridine conjugate targets adenine residues in the DNA minor groove, with covalent binding possibly at the N3 site [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, Bierbach and co-workers have reported the first example of monofunctional adenine adducts being formed by a divalent platinum complex, [PtCl(en)(ACRAMTU-S] (ACRAMTU ¼ 1-[2-(acridin-9-ylamino)ethyl]-1,3-dimethylthiourea), with double-stranded DNA [37]. Furthermore, the authors concluded that the platinum-acridine conjugate targets adenine residues in the DNA minor groove, with covalent binding possibly at the N3 site [37]. Alternatively, given that platinum complexes predominantly form covalent adducts in the DNA major groove, it may be possible to utilise inert octahedral complexes that specifically bind in the DNA major groove in the linking ligand.…”
Section: Discussionmentioning
confidence: 99%
“…1; [PtCl(en)(ACRAM-TUS)](NO 3 ) 2 ; ACRAMTU = 1-[2-(acridin-9-ylamino)-ethyl]-1,3-dimethylthiourea, en = ethane-1,2-diamine) was designed to produce DNA adducts different from those formed by the clinical platinum agents [5]. Using enzymatic and acidic digestion assays we have demonstrated previously that complex 1 forms monofunctional adducts with guanine (G) ($80%) and adenine (A) ($20%) in native DNA [6]. In all of the adducts identified, the chloro leaving group has been replaced with nucleobase nitrogen (G-N7, A-N7, A-N3, or A-N1), while the sulfur-bound intercalator remains attached to the metal, rendering ACRAMTU a typical non-leaving group [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A half-life of adduct formation of 7.5 h was determined from timedependent NMR spectra when 1 mM Pt was incubated with 3 mM of dG at 37°C [10]. In contrast, reactions of conjugate 1 with calf thymus DNA proceed significantly faster and are virtually complete after 12 h [6]. Thus, we speculated that platination of nucleobase nitrogen in double-stranded DNA from a preintercalated state might be kinetically favored over simple ligand substitution in the mononucleoside model system.…”
Section: Introductionmentioning
confidence: 99%